Aldosterone-producing adenoma-harbouring KCNJ5 mutations is associated with lower prevalence of metabolic disorders and abdominal obesity. Issue 12 (26th December 2021) - Chen, Kuan-Ming; Chang, Yu-Ling; Wu, Tung-Hsin; Lee, Bo-Ching; Chen, Po-Ting; Liu, Kao-Lang; Hong, Jia-Sheng; Chang, Chin-Chen; Wu, Vin-Cent; Lin, Yen-Hung
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Aldosterone overproduction and lipid metabolic disturbances between idiopathic hyperaldosteronism (IHA) and unilateral aldosterone-producing adenoma (APA) have been inconsistently linked in patients with primary aldosteronism. Moreover, KCNJ5 mutations are prevalent among APAs and enhance aldosterone synthesis in adrenal cortex. We aimed to investigate the prevalence of metabolic syndrome (MetS) in each primary aldosteronism subtype and observe the role of KCNJ5 mutations among APAs on the distribution of abdominal adipose tissues quantified using computed tomography (CT), including their changes postadrenalectomy. Design and methods: We retrospectively collected 244 and 177 patients with IHA and APA at baseline. Patients with APA had undergone adrenalectomy, and gene sequencing revealed the absence ( n  = 75) and presence ( n  = 102) of KCNJ5 mutations. We also recruited 31 patients with APA who had undergone CT-scan 1-year postadrenalectomy. Results: The patients with APA harbouring KCNJ5 mutations had significantly lower prevalence of MetS and smaller distribution in waist circumference, subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) than the other groups. Logistic regression analysis indicated that the VAT area correlated significantly with KCNJ5 mutations among the APAs. Only participants with KCNJ5 mutations had significant increases in triglycerides, cholesterol, SAT, and VAT after 1-year postadrenalectomy. Conclusion: This study is the first to demonstrate that MetS and abdominal obesity were less prevalent in the patients with APA harbouring KCNJ5 mutations compared with the IHA group and the non- KCNJ5- mutated APA group. Increasing prevalence of dyslipidaemia and abdominal obesity was observed in patients with KCNJ5 mutations 1-year postadrenalectomy.